Phylogenetic Relationships in Eleocharis (Cyperaceae): C-4 Photosynthesis Origins and Patterns of Diversification in the Spikerushes - Roalson, Eric H.; Hinchliff, Cody E.; Trevisan, Rafael; da Silva, Carlos R. M. [UNESP] (Amer Soc Plant Taxonomists, 2010)
Eleocharis (Cyperaceae) is a morphologically and physiologically diverse lineage of 250 + species with a cosmopolitan distribution. We here explore phylogenetic relationships in this lineage using maximum parsimony and Bayesian inference analyses of nrDNA ITS and cpDNA trnC-ycf6 and ycf6-psbM sequence data with the goals of comparing our phylogenetic hypotheses to previous classifications, morphological variation, and photosynthetic pathway variation. Our results suggest that in Eleocharis C, photosynthesis has been derived at least three times, with several cases of possible reversion to C-3-like or intermediate pathways and several additional origins of C-3-C-4 intermediate photosynthetic pathways, as inferred by carbon isotope ratio measurements. Many classification units currently recognized in Eleocharis are not monophyletic, however, E. subgenus Limnochloa and E. subgenus Scirpidium are monophyletic. Other classification units largely corresponding to clades include E. subgenus Zinserlingia, E. subseries Chaetariae, and E. series Maculosae. Problems with species circumscription and morphological variation in several groups are discussed in light of the phylogeny, particularly in the context of species membership of seven focal clades found in the analyses.
Keywords: C-4; classification; Cyperaceae; Eleocharis; photosynthetic pathway evolution